Efficacy and economics of synthetic pyrethroids for the control of leaf-miner (Chromatomyia horticola) on vegetable pea (Pisum sativum) in Kullu valley of Himachal Pradesh - KUMAR, JITENDER; SHARMA, S D; KASHYAP, N P (The Indian Journal of Agricultural Sciences, 2014)
A Held study was carried out dming 1995-99 at Bajaura (Kullu), Himachal Pradesh, to determine the efficacy and economics of monocrotophos (0.036% and 0.02%), cypermethrin (0.0075%), fenvalerate (0.01 %), lambda-cyhalothrin (0.004%), azadirachtin (0.0012%), methyl parathion (0.05%) and a mixture of cypennethrin (0.00375%) and azadirachtin (0.0006%) for the control of leaf-miner [Chramatomyia harticola (Goureau)] on garden pea (Pisum salivum L., s.I.). Monocrotophos at both the doses. 0.036 arid 0.02 %, was the most effectIve and economical treatment with an average net returns of Rs 16.66 and 15.40/rupee invested respectively. It was followed by cypermethrin, lambda-cyhalothrin and fenvalerate with average net returns of Rs 13.89, 11.38 and 1 0.78/rupee Invested respectively. In view of the likely ban on the use of monocrotophos, synthetic pyrethrolds showed promise for the control of C. horticola on pea.